PENANGANAN MAMALIA LAUT TERDAMPAR LUMBA-LUMBA SPOTTED DOLPIN (Stenella attenuata) DI UJONG BATEE - Melinda, Sri; Kusumawati, Ika; Rahma, Endah Anisa (Universitas Mataram, 2024)
This activity is a special activity that uses market research methods in its application, identification using the Rapid Assessment method refers to the Fahmi & White (2006) method. This activity was carried out at the UPTD Water Area Management, Aceh Maritime Affairs and Fisheries Service on September 20 and 21. In this activity the tools used were a digital camera used to record the activity, a field guide